(untitled) (MAUSAM, 2025)
Chief features (i) In the Hot weather season of 2024, only one intense low-pressure system, severe Cyclonic storm, “Remal,” formed over the Bay of Bengal during the season from 24-28 May. Along with this severe cyclonic storm, a low-pressure area formed over the Arabian Sea on 23-24 May. (ii) The hot weather season 2024 with reference to severe heat wave/heat wave conditions was mild but began in the last week of March continued to first week of April and again appeared during last week of April. In the month of May, the heat wave/severe heat wave conditions were observed over northwest, central India and eastern parts of India. (iii) The seasonal rainfall over homogenous region of central India was excess while the country as a whole and remaining three regions recorded normal rainfall. Rainfall for all the months (March to May) for the country was normal to above normal except some sub-divisions from the south peninsula and northwest India where it was deficient. (iv) Thunderstorms/hailstorms were frequent throughout the season over the country. (v) Monsoon advanced into some parts of the Maldives & Comorin area and some parts of the South Bay of Bengal, Nicobar Islands, and South Andaman Sea on 19 May, 2024. It reached Kerala on 30 May, two days prior to its normal date, i.e., 1 June.